Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species - Kumar, Girish P.; Lelej, Arkady S.; Das, Dipanwita; Raveendran, Hanima K.p.; Loktionov, Valery M. (Zootaxa, 2019)
The Oriental genus Kudakrumia Krombein, 1979 is newly reported from India with two species: K. mirabilis Krombein, 1979 (Kerala) and K. rangnekari Girish Kumar & Lelej, sp. nov. (Goa, Kerala). A key to the Oriental genera and species of tribe Kudakrumiini is given.